Adalimumab treatment in patients with rheumatoid arthritis with renal insufficiency. Issue 3 (26th February 2013) - Sumida, Keiichi; Ubara, Yoshifumi; Suwabe, Tatsuya; Hayami, Noriko; Hiramatsu, Rikako; Hasegawa, Eiko; Yamanouchi, Masayuki; Hoshino, Junichi; Sawa, Naoki; Takaichi, Kenmei
Abstract: Objective: To elucidate the safety of adalimumab for rheumatoid arthritis (RA) patients with renal insufficiency, including those with end‐stage renal disease undergoing hemodialysis. Methods: Sixty‐five RA patients, including 2 patients undergoing hemodialysis, treated with adalimumab in our hospital from December 1, 2008 to June 30, 2011 were retrospectively analyzed. Renal function was evaluated by the estimated glomerular filtration rate (eGFR) calculated from the Cockcroft‐Gault formula at the start and end of followup after adalimumab treatment. The proportion of the patients who discontinued or switched adalimumab treatment and the change of the eGFR were compared between patients with (n = 39) and without (n = 26) renal insufficiency, defined as an eGFR <60 ml/minute/1.73 m 2 . Results: There was no significant difference between the 2 groups in the proportion of the patients who discontinued or switched adalimumab treatment (51.3% versus 50.0%; P = 0.53). The mean ± SD changes of eGFR were from 41.6 ± 13.3 to 43.4 ± 17.9 ml/minute/1.73 m 2 in patients with renal insufficiency and from 83.6 ± 17.5 to 83.0 ± 16.8 ml/minute/1.73 m 2 in patients without renal insufficiency, and the differences in each group were not statistically significant ( P = 0.92 and P = 0.78, respectively). No severe infections or other severe adverse events were observed in either group during adalimumab treatment. Conclusion: Our data indicate that adalimumab does not worsen renal function and has no serious adverse events even for RA patients with renal insufficiency, including those undergoing hemodialysis, and suggest that it could be a potential therapeutic option for them.